Quinoline-Based FDA-Approved Drugs: Synthetic Route and Clinical Uses - Chandra, Devesh; Sachin, Sachin; Rav, Shourabh; Sharma, Upendra (Synlett, 2025)
In the last 25 years, the U.S. Food and Drug Administration (FDA) approved 11 new molecular entities (NMEs) comprising quinoline as core moiety. These drugs are primarily used for the treatment of anemia, malaria, hepatitis, and various types of cancer, i.e., lung, breast, kidney, blood, and thyroid. Based on their approval date, a chronological discussion on these marketed drugs is provided. This Perspective summarizes the industrial synthesis, mechanism of action, and clinical uses of the quinoline-based FDA-approved NMEs of the 21st century.1 Introduction2 Quinoline-Based FDA-Approved Drugs2.1 Mitapivat (2022)2.2 Tivozanib (2021)2.3 Capmatinib (2020)2.4 Tafenoquine (2018)2.5 Neratinib (2017)2.6 Lenvatinib (2015)2.7 Simeprevir (2013)2.8 Bosutinib (2012)2.9 Cabozantinib (2012)2.10 Bedaquiline (2012)2.11 Pitavastatin (2009)3 Conclusion4 Abbreviations
Keywords: drugs; FDA; NMEs; quinoline